2014
DOI: 10.1128/mcb.01166-13
|View full text |Cite|
|
Sign up to set email alerts
|

PIASy-Mediated Sumoylation of SREBP1c Regulates Hepatic Lipid Metabolism upon Fasting Signaling

Abstract: e SREBP1c is a key transcription factor that regulates de novo lipogenesis during anabolic periods. However, the molecular mechanisms involved in the suppression of SREBP1c under nutritional deprivation are largely unknown. In this study, we demonstrate that the small ubiquitin-related modifier (SUMO) E3 ligase, a protein inhibitor of activated STAT Y (PIASy), sumoylates SREBP1c at Lys98, leading to suppression of the hepatic lipogenic program upon fasting-induced signals. In primary hepatocytes, ablation of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…, in the lean state. Previous studies have shown that HDAC4 can serve as SUMO E3 ligase for a number of target proteins in various cell types (Ghisletti et al, 2007; Gregoire and Yang, 2005) and that SUMOylation can serve as a priming process for ubiquitination, leading to protein ubiquitination and proteasomal degradation of the target proteins (Lee et al, 2014; Liu et al, 2013; Miteva et al, 2010). Consistent with the findings here, only the nuclear form of HDAC4 possesses SUMO E3 ligase activity (Lee et al, 2009; Yao and Yang, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…, in the lean state. Previous studies have shown that HDAC4 can serve as SUMO E3 ligase for a number of target proteins in various cell types (Ghisletti et al, 2007; Gregoire and Yang, 2005) and that SUMOylation can serve as a priming process for ubiquitination, leading to protein ubiquitination and proteasomal degradation of the target proteins (Lee et al, 2014; Liu et al, 2013; Miteva et al, 2010). Consistent with the findings here, only the nuclear form of HDAC4 possesses SUMO E3 ligase activity (Lee et al, 2009; Yao and Yang, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SREBP-1c deacetylation by SIRT1 has also been reported to promote ubiquitination and proteasomal degradation of SREBP-1c, implicating dual effects of SREBP-1c acetylation 30, 57 . In addition, during nutritional deprivation, PKA mediated SREBP-1c phosphorylation increases its interaction of SREBP-1c with PIASy, the small ubiquitin-related modifier (SUMO) E3 ligase, thus augmenting sumoylation of SREBP-1c at K98, leading to SREBP-1c degradation 58 . These studies further illustrate how different posttranslational modifications of SREBP-1c operate together in regulating lipogenic gene transcription.…”
Section: Regulation Of Srebp-1c Expression and Its Cleavagementioning
confidence: 99%
“…This occurs through the regulation of some of the most fundamental metabolic processes, including energy and nucleotide metabolism, and permits physiological adaptation in response to cellular and environmental queues (Enserink 2015; Makhnevych et al 2009). SUMO has been implicated in complex human diseases and developmental anomalies that are also associated with nutritional and/or metabolic perturbations including Alzheimer’s disease (Dorval and Fraser 2007; Hoppe et al 2015; Lee et al 2013, 2014b; Martins et al 2016; McMillan et al 2011; Sarge and Park-Sarge 2009), Parkinson’s disease (Guerra de Souza et al 2016) (Eckermann 2013; Krumova et al 2011), type I diabetes (Li et al 2005; Wang and She 2008), familial partial lipodystrophy (Simon et al 2013), diabetes-mediated cardiovascular disease (Chang and Abe 2016), congenital heart disease (Wang et al 2011), cardiomyopathy (Kim et al 2015c; Zhang and Sarge 2008), arthritis (Yan et al 2010), amyotrophic lateral sclerosis (Dangoumau et al 2016; Foran et al 2013; Niikura et al 2014), and cleft lip and/or palate (Alkuraya et al 2006; Song et al 2008; Tang et al 2014). …”
Section: 1 Introduction: Functions Of Sumo In Metabolismmentioning
confidence: 99%